2021
DOI: 10.1097/cm9.0000000000001305
|View full text |Cite
|
Sign up to set email alerts
|

Comparable efficacy of 100 mg aspirin twice daily and rivaroxaban for venous thromboembolism prophylaxis following primary total hip arthroplasty: a randomized controlled trial

Abstract: Background: Aspirin has demonstrated safety and efficacy for venous thromboembolism (VTE) prophylaxis following total hip arthroplasty (THA); however, inconsistent dose regimens have been reported in the literature. This study aimed to evaluate and compare the safety and efficacy of 100 mg aspirin twice daily with rivaroxaban in VTE prophylaxis following THA. Methods: Patients undergoing elective unilateral primary THA between January 2019 and January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The subgroup analysis of elective surgery also reported the same result (RR = 0.81, 95% CI: 0.34-1.91, P = 0.63) (Fig. 7) (17,19,20,21,22,23,24). Among…”
Section: Secondary Outcomes (Mortality Bleeding Events and Wound Comp...supporting
confidence: 60%
See 2 more Smart Citations
“…The subgroup analysis of elective surgery also reported the same result (RR = 0.81, 95% CI: 0.34-1.91, P = 0.63) (Fig. 7) (17,19,20,21,22,23,24). Among…”
Section: Secondary Outcomes (Mortality Bleeding Events and Wound Comp...supporting
confidence: 60%
“…Furthermore, the wound complications in the subgroup analysis of elective surgery also showed no significant difference (RR = 0.57, 95% CI: 0.19-1.75, P = 0.33) (Fig. 9) (17,19,20,21,22,23,24). Haac et al reported that 12 of 165 patients in the aspirin group and 15 of 164 patients in the LMWH group had wound complications after trauma surgery (18).…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…Table 1 summarizes the characteristics of included studies. The daily dosage of aspirin was 100 mg in six studies [ 5 8 , 21 , 23 ], 81 mg daily in two studies [ 25 , 26 ], 200 mg in one study [ 22 ], and 81–324 mg in one study [ 9 ]. The included studies had follow-up periods ranging from 1 to 23 months.…”
Section: Resultsmentioning
confidence: 99%
“…1). Eleven studies reporting 10 RCTs involving 57,645 patients were included in this analysis [5][6][7][8][9][21][22][23][24][25][26]. A study conducted by Anand et al [27] was excluded as it included patients with stable peripheral or carotid artery disease whose data were included in the study by Eikelboom et al [6].…”
Section: Resultsmentioning
confidence: 99%